Manfaat Pemisahan Sampah Organik dan Anorganik Melalui Media Buku Ilustrasi Anak - Suseno, Ardani Ari; Albab, Nabila Ulul; Martadireja, Sonde (Besaung : Jurnal Seni Desain dan Budaya)
Garbage was defined as the residue of people's daily activities. In the social environment, to facilitate decomposition, garbage was generally grouped into two simple parts; namely organic garbage and inorganic garbage. garbage management was needed to reduce the possibility of positive and negative impacts to the environment. Economic value was grouped into positive impact, while the source of odors and disease clusters were grouped as negative impact. In this study, the focus of the problem is on the negative group. Because if garbage is allowed to pile up in one place in community settlements, it will become a source of unpleasant odors so that it can then become an area for germs to develop. This condition is an indication that the garbage had not been managed properly and could worsen the surrounding environment. Therefore, proceeded from the scientific visual communication design, then at least hazard information and proper garbage processing method needed to be made. Knowledge of garbage separation to reduce environmental pollution would be better if known or understood since childhood. The choice of work form for dissemination of this information was children illustration book. The process of realizing this illustration book work used several stages, the first stage was the process of collecting data about garbage and its processing, then data on the type of book that match the target audience. The second stage was the process of making books, in this stage it went through several processes from pre-production to production.